THE TEACHER’S ABILITY IN MAKING HOTS QUESTIONS IN THE THEMATIC LEARNING CONTENT OF SOCIAL STUDIES - Fikri, Alfarobi Brillian; Susapti, Peni; Setya, Makhasin Ariffi (AULADUNA: Jurnal Pendidikan Dasar Islam, 2021)
Abstract This study aims to describe the teachers’ abilities and obstacles in making HOTS questions in the thematic learning of social studies for class V at MI Jombor, Semarang. This study used a descriptive research method with data collection techniques through interviews, observation, and documentation. The results of this study concluded that: (1) the teachers did not have good understanding and ability in making HOTS questions of the thematic learning of social studies, and (2) MI Jombor had not been able to apply the curriculum 2013, which was oriented to HOTS learning and the teachers still had problems in making HOTS questions in the thematic learning of social studies. These findings need the teachers’ concern. In other words, 21st-century learning requires teachers to continuously improve their innovation and creativity in making quality evaluation questions for their students. Abstrak Penelitian ini bertujuan untuk mendeskripsikan kemampuan dan kendala guru dalam pembuatan soal HOTS pada pembelajaran tematik muatan IPS kelas V di MI Jombor, Semarang. Penelitian ini menggunakan metode penelitian deskriptif dengan teknik pengumpulan data wawancara, observasi, dan dokumentasi. Hasil penelitian ini menyimpulkan bahwa (1) guru belum mempunyai pemahaman dan kemampuan yang baik dalam pembuatan soal HOTS pada pembelajaran tematik muatan IPS, dan (2) MI Jombor belum mampu menerapkan kurikulum 2013 yang berorientasi pada pembelajaran HOTS dan guru masih mengalami kendala dalam pembuatan soal HOTS pada pembelajaran tematik muatan IPS. Hal ini menjadi catatan yang perlu diperhatikan oleh guru. Dengan kata lain, pembelajaran abad 21 menghendaki guru untuk selalu meningkatkan inovasi dan kreativitasnya dalam membuat soal evaluasi yang berkualitas bagi siswanya.